2007
DOI: 10.1038/nsmb1275
|View full text |Cite
|
Sign up to set email alerts
|

A novel tripartite motif involved in aquaporin topogenesis, monomer folding and tetramerization

Abstract: Aquaporin (AQP) folding in the endoplasmic reticulum is characterized by two distinct pathways of membrane insertion that arise from divergent residues within the second transmembrane segment. We now show that in AQP1 these residues (Asn49 and Lys51) interact with Asp185 at the C terminus of TM5 to form a polar, quaternary structural motif that influences multiple stages of folding. Asn49 and Asp185 form an intramolecular hydrogen bond needed for proper helical packing, monomer formation and function. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 50 publications
3
72
2
Order By: Relevance
“…Interestingly, AQP1 proved to be the most sensitive substrate for perturbations of OST-mediated protein N-glycosylation using our in vitro assay. This most likely reflects the fact that the glycosylation of Asn-42 of AQP1 is complex, and relies on the initial translocation of TM2 into the ER lumen prior to the subsequent topological maturation of the precursor into its final structure (Buck et al, 2007;Foster et al, 2000). Our studies of protein N-glycosylation using a cell-based system bear out this model.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, AQP1 proved to be the most sensitive substrate for perturbations of OST-mediated protein N-glycosylation using our in vitro assay. This most likely reflects the fact that the glycosylation of Asn-42 of AQP1 is complex, and relies on the initial translocation of TM2 into the ER lumen prior to the subsequent topological maturation of the precursor into its final structure (Buck et al, 2007;Foster et al, 2000). Our studies of protein N-glycosylation using a cell-based system bear out this model.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore the N-and C-terminal domains of AQP1 are thought to be involved in its tetramer formation (2-4, 20, 21). Recently, it has also been reported that although the residues are unique to AQP1, Lys 51 of TM2 interacts with Asp 185 of TM5 on an adjacent monomer to stabilize the AQP1 tetramer (22). Because the degree of amino acid sequence similarity between AQP11 and other AQPs is rather low, it is difficult to predict the three-dimensional structure of AQP11 using homology modeling (7).…”
Section: Discussionmentioning
confidence: 99%
“…Oligomer formation is the prerequisite for the function of several channels, receptors, and transporters. In particular, the tetramer formation of aquaporin is critical to its water permeability and ion selectivity (52)(53)(54), whereas each aquaporin subunit has a water channel in the center. We speculate that the interaction of dSPP/NT resulted in a conformational change of each subunit that affects the formation and/or the stability of the dSPP tetramer, thereby causing the dominant negative effect (Fig.…”
Section: Discussionmentioning
confidence: 99%